The University between Theory and Practice. How Romanian Aspiring University Leaders Understand the University - Sonia Pavlenko; Cristina Bojan (University Babes-Bolyai, 2017)
The debate regarding the essence of the university has been going on for centuries. Certain elements of its definition may be age (or century) -specific, illustrating the university's adaptation to the contemporary needs of the society, while others are invariable throughout the centuries. Therefore, it is always a challenge to define the common elements defining the university, applicable at the time of investigation. Our article focuses on the question: How do individuals running for leadership positions in Romanian higher education see/understand the university?. We consider them to be highly informed actors in this field, and their views are a well-informed source of primary information. Firstly, the article reviews existing approaches and definitions of a university, trying both to identify is specifically as a higher education institution and to distinguish it from potentially similar institutions. Then, through qualitative analysis of selected electoral manifestos, it identifies a number of characteristics of the institution. Based on the characteristics identified, the article discusses possible implications of the findings for the Romanian higher education field